A surface‐in gradient of thalamic damage evolves in pediatric multiple sclerosis. Issue 3 (20th February 2019) - Fadda, Giulia; Brown, Robert A.; Magliozzi, Roberta; Aubert‐Broche, Berengere; O'Mahony, Julia; Shinohara, Russell T.; Banwell, Brenda; Marrie, Ruth Ann; Yeh, E. Ann; Collins, D. Louis; Arnold, Douglas L.; Bar‐Or, Amit; et al.
Abstract : Objective: Central nervous system pathology in multiple sclerosis includes both focal inflammatory perivascular injury and injury to superficial structures, including the subpial region of the cortex, which reportedly exhibits a gradient of damage from the surface inward. We assessed how early in the multiple sclerosis course a "surface‐in" process of injury suggesting progressive biology may begin. Methods: We focused on the thalamus, which notably has both a cerebrospinal fluid (CSF) interface and a white matter interface. Thalamic volume trajectories were assessed in a prospectively followed cohort of children from initial presentation with either multiple sclerosis or monophasic acquired demyelination, and healthy controls. Voxelwise volume changes were calculated using deformation‐based morphometry, and analyzed in relation to distance from the CSF interface by mixed effects modeling and semiparametric smoothing methods. Results: Twenty‐seven children with multiple sclerosis and 73 children with monophasic demyelination were prospectively followed with yearly brain scans (mean follow‐up = 4.6 years, standard deviation = 1.9). A total of 282 healthy children with serial scans were included as controls. Relative to healthy controls, children with multiple sclerosis and children with monophasic demyelination demonstrated volume loss in thalamic regions adjacent to the white matter. However, only children with multiple sclerosis exhibited an additional surface‐in gradient of thalamic injury on the ventricular side, which was already notable in the first year of clinical disease (asymptote estimate = 3.01, 95% confidence interval [CI] = 1.44–4.58, p = 0.0002) and worsened over time (asymptote:time estimate = 0.33, 95% CI = 0.12–0.54, p = 0.0021). Interpretation: Our results suggest that a multiple sclerosis disease‐specific surface‐in process of damage can manifest at the earliest stages of the disease. ANN NEUROL 2019;85:340–351.